Iron oxide Nanoparticles; A Review on the role of Transition Metal doping on its magnetic properties and particle size for imaging and therapeutic applications - Izunna Stanislaus Okeke; Eugene Odinakachi Echeweozo; Amoge Chidinma Ogu; Priscilla Yahemba Aondona; Fabian I. Ezema (Hybrid Advances)
Iron oxide nanoparticles (IO-NPs) are one of the remarkable materials for diagnostic and therapeutic applications. However, its applications are still facing a good number of challenges. Hence, there is growing interest in modifying IO-NPs properties to enhance their applicability. In this review, the effect of Transition Metal (TM) doping on the IO-NPs magnetic properties and particle sizes as well as its role in IO-NPs imaging and therapeutic applications was discussed.Reviewed articles show that doping IO-NPs with TM alters their magnetic properties and particle size. In imaging, this had led to significant effects on IO-NPs relaxometric parameters and ultimate improvement in image contrasts in MRI. Gold-doped IO-NPs indicated improved performance in tumor catalytic and x-ray radiation therapy. Furthermore, research findings revealed that TM provides the opportunity for temperature control in IO-NPs hyperthermia application. The findings from the reviewed papers suggest that TM doped IO-NPs can be critical in enhancing applications of IO-NPs in hyperthermia, drug delivery diagnostics, and therapeutics.